Prevalence of non-communicable disease and their life style risk factors among elderly in India: an analysis of WHO SAGE data - Harikumar, Reshma; Sreena, T. V. (International Journal Of Community Medicine And Public Health, 2025)
Background: Non communicable diseases (NCDs) are an important global health concern, especially among older adults. Understanding the prevalence and lifestyle factors contribute to NCD will help to tailor specific interventions in young age to prevent the NCDs in the old age. Methods: Cross sectional study, secondary analysis of nationally representative data from WHO study on global AGEing and adult health (SAGE). The total sample size taken for analysis is 3971 considering only age group 60 years and above. Results: Prevalence of NCDs were stroke (2.6%), angina (5.1%), diabetes (7.2%), chronic lung disease (4.2%), asthma (7.9%) and depression (4,3%). Significant associations were found between tobacco and alcohol consumption with depression, chronic lung disease and asthma. Vegetable and fruit consumption were associated with diabetes. Conclusions: Study highlights a strong association of lifestyle factors on NCDs among the old age population in India. Interventions targeting substance abuse dietary habit and physical activity are important for reducing the growing burden of NCDs in India.